The influence of the velocity of agitation in the dynamic leaching of altered minerals - Romero Baylón, Alfonso (2009)
The study called Velocity of agitation in the dinamic leaching by altered minerals, has been made with the purpose of determining the influence of the velocity of agitation of the equipment of leaching for the recovery of precious metals from the tailings with high gold content. It`s well know, the recovery of valid metal of gold such as other metals valids from the point of view of economy, which are more valuable in certain grade because of the constant increment of metal’s prices. On the other hand, the dependent variable of operation that correspond to the recovery, which has been studied with regard to the main independent variable of operation which has been sintetized for the velocity of rotation or agitation (rpm) of equipment of dynamic leaching, that has been employed in the dynamic cyanidation of altered minerals employed, in this particular case, the tailings from Ticapampa. In that sense, this paper include the study of the treatment of benefit of polymetallic sulfide tailing from Ticapampa, which has been carried out for Experimental Tests of laboratory scale, that included metallurgy processes such as: leaching by cyanidation with the aim of obtaining the recovery of precious metals of gold present in the tailing of Ticapampa.